Senzor višine gladine s prepletenima optičnima vlaknoma - Suhadolnik, Alojz (Informacije MIDEM, 1992)
A new type of optical fiber continouous liquid level sensor was made. The basic principle is light transmission between input and output fiber, which are stripped and twisted together. In this contribution, sensor structure, liquid level measurements and refractive index measurements are described. The effect of wetting and the liquid absorption influence on the sensor response are also investigated.
Keywords: absorpcija; absorption; eksperimentalne raziskave; experimental research; liquid film; liquid level measurement; liquid level sensors; merjenje lomnega količnika; merjenje nivoja tekočin; optical fibres; optical sensors; optična vlakna; optični senzor; refractive index measurement; senzorji nivoja tekočin; tekočinski film